Motivations for physical activity - literature review - Góreczna, Aleksandra; Garczyński, Wojciech (Journal of Education, Health and Sport, 2017)
Physical activity is in its own way a kind of treatment of some diseases and the factor that can reduce the risk of their occurrence. For instance, taking care of your condition on a regular basis may reduce the risk of developing cardiovascular system diseases. Physical activity proves helpful in many areas levels of human life. It has a huge impact on well-being, health and apperance. Also, It can be a form of escaping from everyday problems. There is a variety of processes that take place in human body during exercising. It appears that people’s awareness about its beneficial effect on health is growing from year to year. Physical education classes should teach children from an early age the advantages of being active. Everyone should take up any form of physical activity at least several Times a week and continue the habit throughout whole life.